Can mixed singing facilitate coexistence of closely related nightingale species?. (18th April 2018) - Souriau, Abel; Kohoutová, Hana; Reif, Jiří; Vokurková, Jana; Petrusek, Adam; Reifová, Radka; Petrusková, Tereza
Abstract : Mixed singing in songbirds is usually considered to result from erroneous learning from other species, but we suggest it might be rather adaptive. Our results show that mixed singing of Thrush Nightingale males, which incorporate songs of the Common Nightingale in their repertoires in areas where both species co-occur, may help these 2 species to establish boundaries of their territories, and thus facilitate their coexistence before divergence in ecological niches evolves. Abstract: Knowledge of the mechanisms facilitating the coexistence of closely related competing species is crucial for understanding biodiversity patterns. The concept of convergent agonistic character displacement (ACD) suggests that interspecific interference competition may lead to convergence in territorial signals between species, which helps to establish interspecific territoriality and thus facilitate the species coexistence. Despite a strong theoretical background, however, empirical evidence for convergent ACD in nature is still scarce. Here we tested whether mixed singing (i.e. copying of elements from songs of a closely related sympatric species) in the Thrush Nightingale ( Luscinia luscinia ) in a secondary contact zone with the Common Nightingale ( L. megarhynchos ) could represent a case of convergent ACD. Using playback experiments, we measured the intensity of physical and vocal territorial responses of Common Nightingale males to 3 stimuli: conspecific song, pure heterospecific song, and mixed heterospecific song of the Thrush Nightingale. We found that Common Nightingale males showed a stronger physical territorial response to conspecific than both pure and mixed heterospecific songs. However, the intensity of vocal territorial response significantly increased with the presence of Common Nightingale elements in the stimuli, being lowest to pure heterospecific songs, intermediate to mixed heterospecific songs, and strongest to conspecific songs. These results indicate that mixed singing in the Thrush Nightingale may indeed be a case of convergent ACD. Our findings highlight the potential importance of mixed singing in facilitating species coexistence in the early stages of divergence.